2007
DOI: 10.1080/07315724.2007.10719609
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Nucleated Red Blood Cells in Infants of Overweight and Obese Mothers

Abstract: Infants of overweight and obese mothers have increased nucleated red blood cells at birth compared with controls. We speculate that even apparently healthy fetuses of overweight and obese mothers are exposed to a subtle hypoxemic environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…25,26 In a previous study, we reported that infants of overweight and obese mothers have increased circulating absolute nucleated red blood cells counts at birth compared with infants of non-obese mothers. 6 The current findings support our theory that elevation of circulating absolute nucleated red blood cells counts in infants of overweight and obese mothers was due to increased production of fetal EPO. This theory is also supported by the fact that infants of obese mothers are at a higher risk for intrauterine fetal death.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…25,26 In a previous study, we reported that infants of overweight and obese mothers have increased circulating absolute nucleated red blood cells counts at birth compared with infants of non-obese mothers. 6 The current findings support our theory that elevation of circulating absolute nucleated red blood cells counts in infants of overweight and obese mothers was due to increased production of fetal EPO. This theory is also supported by the fact that infants of obese mothers are at a higher risk for intrauterine fetal death.…”
Section: Discussionsupporting
confidence: 88%
“…[3][4][5] In a previous study, we reported that infants of overweight and obese mothers have increased circulating absolute nucleated red blood cell counts at birth compared with infants of non-obese mothers. 6 We then speculated that fetal hypoxia was responsible for both the elevation of circulating absolute nucleated red blood cells (through increased production of fetal erythropoietin (EPO)) and the elevated risk for 'unexplained' intrauterine fetal death.We thus designed this study to examine the hypothesis that maternal body mass index (BMI) (an index of maternal adiposity) correlates with cord blood concentrations of EPO. …”
mentioning
confidence: 99%
“…In rodents, hypoxia downregulates MME expression in the lungs, kidneys [20], and in the brain [21]. In fact, several studies have revealed a subtle hypoxic fetal environment in pregnancy complicated by maternal overweight [29,30]. Additionally, MME is downregulated by NF-κB pathway via microRNA miR155 in B-lymphoma cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…We then conducted a backward stepwise regression analysis to assess whether EPO (dependent variable) could be influenced by the duration of ruptured membranes while taking into account possible confounding variables such as gestational age, 1-or 5-minute Apgar scores, or maternal body mass index (BMI). 14 In this analysis again, EPO was not influenced by duration of ruptured membranes and only maternal BMI was weakly, but…”
Section: Resultsmentioning
confidence: 58%